2021
DOI: 10.1108/md-11-2020-1485
|View full text |Cite
|
Sign up to set email alerts
|

Empowering leadership and employees' work engagement: a social identity theory perspective

Abstract: PurposeThis study aims to explore mediational mechanisms and conditions by which empowering leadership leads to positive outcomes at the employee level. Using social identity theory (SIT) as a foundation, the authors present an integrated moderated mediation model to explain the interactive effects of empowering leadership and leaders' prototypicality on employees' work engagement through the mediation of organizational identification (OI).Design/methodology/approachThe research model was tested using multilev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 98 publications
(219 reference statements)
3
34
0
Order By: Relevance
“…Thus, the response rate was 73.3%. This response rate is consistent with several previous studies conducted at the individual level (Arshad et al. , 2022; Li et al.…”
Section: Methodssupporting
confidence: 93%
“…Thus, the response rate was 73.3%. This response rate is consistent with several previous studies conducted at the individual level (Arshad et al. , 2022; Li et al.…”
Section: Methodssupporting
confidence: 93%
“…Spreitzer (1995) conducted a survey with Fortune 50 mid-level and found similar results, where high levels of performance feedback were related to high levels of motivation. Recent research has shown that supervisor interaction (Huh and Lee, 2022) and empowerment (Arshad et al ., 2021), including performance feedback, positively impact workers' engagement.…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…In line with this view, some scholars advocate that managers should identify the workforce's vision regarding their particular interests, which can either favor or conflict with a strategic priority (Pranjal and Sarkar, 2020). By doing so, managers are using the empowering leadership approach to recognize their workforce's daily work by inviting them to participate in decision-making activities (Arshad et al ., 2022). They are also creating the environment required to develop a shared manager-employee consensus (Bragaw and Misangyi, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The principal source of opposition to the deletion of a product or brand often comes from within the company itself. To alleviate this opposition, managers may adopt an empowering leadership approach, defined as behaviors whereby managers share decision-making duties with their subordinates (Srivastava et al ., 2006; Arshad et al ., 2022). By doing so, managers help to achieve a climate of consensus which can prove critical for successful implementation.…”
Section: Introductionmentioning
confidence: 99%